Higiene perorangan dan karakteristik orang tua pada kejadian infeksi kecacingan siswa sekolah dasar - Fitria Eka Putri; Lucky Herawati; Sitti Rahmah Umniyati (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Personal hygiene, parents’ characteristics and worm infection among elementary school students in Gunung Kidul PurposeThe study aimed to analyze the correlation between individual hygiene of the students and characteristics of the student’s parents, and the worm infestation infection among state elementary school students in Gunung Kidul Regency.MethodsThe design of the study was cross-sectional while the sampling technique was by purposive sampling. Respondents of the research were the third to fifth grade students from four elementary schools. Primary data gathering was conducted from April to May 2016, using observation and questionnaire pages as the instruments. The data analysis was performed using Fisher Exact test with confidence level of 95% and alpha= 0.05.ResultsThe results of the research show the prevalence of STH in Belik, Kropak, Gesing and Tepus I students, which was 2.7%. In the bivariate analysis, the variable which has significant relation with worm infestation infection is mother’s knowledge with PR= 0.91 (95% CI=0.82-1.02; p=0.035).ConclusionThis research suggests that public health center and school need to improve health promotion in elementary school children and mothers about clean and healthy life behavior.